1997
DOI: 10.1002/j.1552-4604.1997.tb04332.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cola Beverage on the Bioavailability of Itraconazole in the Presence of H2 Blockers

Abstract: Thirty-three healthy individuals participated in an open-label, randomized, three-way crossover study designed to compared the bioavailability of a single 200-mg oral dose of itraconazole when administered alone or after treatment with ranitidine, both with and without coadministration of a cola beverage. Each treatment phase was separated by a 2-week washout period. Participants pretreated with ranitidine were required to have a gastric pH of at least 6.0 before receiving itraconazole. An analysis of the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 5 publications
3
69
1
3
Order By: Relevance
“…The acceleration of transit through the gastrointestinal tract would result in reduced absorption of drugs [19]. Drugs that increase gastric pH (e.g., H 2 antagonists and proton pump inhibitors) could slow the dissolution of the solid dosage forms of other drugs such as ketoconazole and itraconazole [11,20] and decrease drug available for absorption in the intestinal lumen. Other pharmacokinetic studies have documented 30-60% reductions in serum itraconazole concentrations (C max , AUC 0-24 ) in healthy volunteers administered itraconazole capsules with either famotidine or omeprazole [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration of transit through the gastrointestinal tract would result in reduced absorption of drugs [19]. Drugs that increase gastric pH (e.g., H 2 antagonists and proton pump inhibitors) could slow the dissolution of the solid dosage forms of other drugs such as ketoconazole and itraconazole [11,20] and decrease drug available for absorption in the intestinal lumen. Other pharmacokinetic studies have documented 30-60% reductions in serum itraconazole concentrations (C max , AUC 0-24 ) in healthy volunteers administered itraconazole capsules with either famotidine or omeprazole [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole is a triazole antifungal, with activity against Candida species (including some fluconazole- 53 or vitamin C drink 54 ) at low gastric pH. Oral itraconazole solution has increased bioavailability (B30-35%) compared with the capsules, but in contrast to the capsules, is maximally absorbed during fasting.…”
Section: Triazole Antifungalsmentioning
confidence: 99%
“…We hypothesize that this bio-variable nature of itraconazole may be partly responsible for the observed anomalous behaviour. Additionally, the pharmacokinetics of orally administered itraconazole in plasma are dose dependent, and absorption from the gastrointestinal tract is affected by various factors, such as food intake versus fasting state (30,31), gastric pH (32,33), drug interactions (33,34), AIDS and the pharmaceutical formulation of the drug (35,36). As per our power calculations, we found that the % CV in the subjects for the innovator product was in excess of 35%, and as per the reported statistical calculations, the number of patients must be more than 85.…”
Section: Discussionmentioning
confidence: 99%